Biocompatibility and Application of Carbon Fibers in Heart Valve Tissue Engineering - Tseng, Yuan-Tsan; Grace, Nabil F.; Aguib, Heba; Sarathchandra, Padmini; McCormack, Ann; Ebeid, Ahmed; Shehata, Nairouz; Nagy, Mohamed; El-Nashar, Hussam; Yacoub, Magdi H.; Chester, Adrian; Latif, Najma (Frontiers in Cardiovascular Medicine, 2021)
The success of tissue-engineered heart valves rely on a balance between polymer degradation, appropriate cell repopulation, and extracellular matrix (ECM) deposition, in order for the valves to continue their vital function. However, the process of remodeling is highly dynamic and species dependent. The carbon fibers have been well used in the construction industry for their high tensile strength and flexibility and, therefore, might be relevant to support tissue-engineered hearts valve during this transition in the mechanically demanding environment of the circulation. The aim of this study was to assess the suitability of the carbon fibers to be incorporated into tissue-engineered heart valves, with respect to optimizing their cellular interaction and mechanical flexibility during valve opening and closure. The morphology and surface oxidation of the carbon fibers were characterized by scanning electron microscopy (SEM). Their ability to interact with human adipose-derived stem cells (hADSCs) was assessed with respect to cell attachment and phenotypic changes. hADSCs attached and maintained their expression of stem cell markers with negligible differentiation to other lineages. Incorporation of the carbon fibers into a stand-alone tissue-engineered aortic root, comprised of jet-sprayed polycaprolactone aligned carbon fibers, had no negative effects on the opening and closure characteristics of the valve when simulated in a pulsatile bioreactor. In conclusion, the carbon fibers were found to be conducive to hADSC attachment and maintaining their phenotype. The carbon fibers were sufficiently flexible for full motion of valvular opening and closure. This study provides a proof-of-concept for the incorporation of the carbon fibers into tissue-engineered heart valves to continue their vital function during scaffold degradation.